2019
DOI: 10.31234/osf.io/dwxb6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semantic transparency effects in German compounds: A large dataset and multiple-task investigation

Abstract: In the present study, we provide a comprehensive analysis and a multi-dimensional dataset of semantic transparency measures for 1,810 German compound words. Compound words are considered semantically transparent when the contribution of the constituents’ meaning to the compound meaning is clear (as in airport), but the degree of semantic transparency varies between compounds (compare strawberry or sandman). Our dataset includes both compositional and relatedness-based semantic transparency measures, also diffe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…These findings are also in line with theoretical accounts of compound words such as the dual‐route (Pollatsek, Hyönä, & Bertram, 2000), multiple‐route (Kuperman, Schreuder, Bertram, & Baayen, 2009) and CAOSS (Composition as Abstract Operation in Semantic Space) ( Günther & Marelli, 2019, Günther, Marelli, & Bölte, 2020; Marelli, Gagne, & Spalding, 2017) models. The first two models posit that compound words are processed via both a compositional route, in which each constituent is identified separately and then combined to form the compound, and a direct lookup route that accesses a unified lexical entry for the whole compound.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are also in line with theoretical accounts of compound words such as the dual‐route (Pollatsek, Hyönä, & Bertram, 2000), multiple‐route (Kuperman, Schreuder, Bertram, & Baayen, 2009) and CAOSS (Composition as Abstract Operation in Semantic Space) ( Günther & Marelli, 2019, Günther, Marelli, & Bölte, 2020; Marelli, Gagne, & Spalding, 2017) models. The first two models posit that compound words are processed via both a compositional route, in which each constituent is identified separately and then combined to form the compound, and a direct lookup route that accesses a unified lexical entry for the whole compound.…”
Section: Discussionsupporting
confidence: 83%
“…At the surface level, compounds can take different forms, and the variations seen in forms mostly depend upon the language in question. In German, compounds are consistently written as a single string/single word (Günther et al, 2020;Zwitserlood et al, 2002). In English, compounds are made of free lexemes, and typically a combination of two or more constituent words (Dressler, 2006), which results in single lexicalized expressions (Juhasz et al, 2003)-compare for example tree house in English with Baumhaus in German.…”
mentioning
confidence: 99%
“…In English, German or Dutch, compound words are right-headed (Koester & Schiller, 2008), that is to say that the second constituent (rightmost) determines the semantic category and the morphosyntactic features of the whole compound-it serves as the head (Juhasz, 2018). The first constituent serves as a modifier which further specifies the meaning as, for instance, in airport, which is a kind of port dedicated to travel by air (Günther et al, 2020). In Bulgarian, compounds are always right-headed (Jarema et al, 1999).…”
mentioning
confidence: 99%
“…In a previous study, Günther and Marelli (2016) demonstrated that the contributions of the constituent meanings to the combined meaning predict explicit sensibility ratings for compound words, including novel compounds (collected by Graves et al, 2013). However, it has been demonstrated that such off-line explicit ratings for complex words are not necessarily affected by the same semantic variable as, especially when only the latter ones are obtained under time pressure (Günther et al, in press; Marelli & Baroni, 2015). The present study therefore aims at systematically investigating how these constituent contributions affect the processing times of novel compounds.…”
mentioning
confidence: 99%
“…In this distributional framework, the Compounding as Abstract Operation in Semantic Space (CAOSS) model (Marelli et al, 2017) is designed to compute the compositional meaning of compounds from its constituents (see the Methods section of Experiment 1). The contribution of either constituent to the compositional process is then measured as their respective similarity to this compositionally obtained representation (Günther & Marelli, 2016, 2019) The CAOSS model has been successfully established as predicting processing times in existing compounds (with higher constituent contributions resulting in faster processing; Günther et al, in press; Günther & Marelli, 2019) and relational effects in novel compounds (Gagné, 2001; Gagné & Shoben, 1997; as reported in Marelli et al, 2017).…”
mentioning
confidence: 99%